The way of the bear [large-type] - Hillerman, Anne, 1949- (Hillerman, Tony. Leaphorn and Chee novel., 2023)
When two suspicious deaths occur in the Bears Ears area, Navajo Tribal Police officers Jim Chee and Bernadette Manuelito must use all their experience, skill, and intuition to find justice.